Proteomic Profiling of Androgen-independent Prostate Cancer Cell Lines Reveals a Role for Protein S during the Development of High Grade and Castration-resistant Prostate Cancer - Saraon, Punit (American Society for Biochemistry and Molecular Biology, 2012)
Androgen deprivation constitutes the principal therapy for advanced and metastatic prostate cancers. However, this therapeutic intervention usually results in the transition to a more aggressive androgen-independent prostate cancer. The elucidation of molecular alterations during the progression to androgen independence is an integral step toward discovering more effective targeted therapies. With respect to identifying crucial mediators of this transition, we compared the proteomes of androgen-independent (PC3, DU145, PPC1, LNCaP-SF, and 22Rv1) and androgen-dependent (LNCaP and VCaP) and/or normal prostate epithelial (RWPE) cell lines using mass spectrometry. We identified more than 100 proteins that were differentially secreted in the androgen-independent cell lines. Of these, Protein S (PROS1) was elevated in the secretomes of all of the androgen-independent prostate cancer cell lines, with no detectable secretion in normal and androgen-dependent cell lines. Using quantitative PCR, we observed significantly higher (p < 0.05) tissue expression levels of PROS1 in prostate cancer samples, further indicating its importance in prostate cancer progression. Similarly, immunohistochemistry analysis revealed elevation of PROS1 in high grade prostate cancer (Gleason grade ≥8), and further elevation in castration-resistant metastatic prostate cancer lesions. We also observed its significant (p < 0.05) elevation in high grade prostate cancer seminal plasma samples. Taken together, these results show that PROS1 is elevated in high grade and castration-resistant prostate cancer and could serve as a potential biomarker of aggressive disease.